Real effects of financial market integration: Evidence from an ECB collateral framework change - Pia Hüttl; Matthias Kaldorf (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
Does central bank collateral policy contribute to financial market integration? We address this question by exploiting that, in 2007, the European Central Bank replaced national collateral frameworks by a single list. Under the single list regime, euro area banks could pledge all euro area bank loans as collateral, not only domestic loans as before the framework change. Banks holding a large share of newly eligible cross-border bank loans increase loan supply compared to banks with smaller holdings to such loans. The additional credit supply is predominately targeted at previously eligible domestic borrowers, suggesting only a small effect on financial integration. However, we find evidence that firms which are highly exposed to affected banks experience a relaxation of borrowing constraints and increase their real activity. The effects of harmonized collateral policy, thus, closely resemble the effects of expansionary credit policy, while it was less successful in stimulating direct cross-border lending.
Keywords: E44; E58; G21; 330; Collateral Policy; Bank Lending Channel; Financial Integration; Real Effects